Edukasi dan Pengolahan Tanaman Toga Kumis Kucing Sebagai Terapi Komplementer di Banjar Sila Dharma Mengwitani Badung - Yasa, gede Trima (Jurnal Abdi Mahosada, 2023)
Indonesian Institute of Sciences in 2019, stated that approximately 29,477 plant species were taxonomically identified. This data shows that 9.47% of the total species in the world found in Indonesia. These plants were empirically use by Indonesian ancestor to promotes health and cure various diseases. This medicinal plant is well known to as family medicinal plant (TOGA, Tanaman Obat Keluarga). Family medicinal plants (TOGA) are home-cultivated plants that are efficacious as medicine. This community service using presentation method, delivered by the lecturers of clinical and community pharmacy undergraduate study program. Furthermore, the level of understanding of participants were measured using the pretest and posttest methods. The result of pretest and posttest tests revealed a significant increase in respondents' knowldege regarding toga plant education. Pretest data shows that 46% of respondents understand material related to the use of TOGA, and in the posttest results it is found that 89% of respondents understand material related to the use of TOGA. Significant increase also found in respondents' knowledge level about use of cat's whiskers leaves as a complementary therapy. Pretest data shows that 20% of respondents know about the use of cat's whiskers leaves as a complementary therapy, and in the posttest data show that 85% of respondents understand material related to the use of cat's whiskers leaves as a complementary therapy..